Optimalisasi OPTIMALISASI MANAJEMEN PENGELOLAAN ZAKAT, INFAQ, DAN SHADAQAH (ZIS) PADA MASJID BAKTI KOTA PALEMBANG - Witriya Alfiani; Mail Hilian Bathin; Safira Elfadhilah (Growth, 2026)
The management of Zakat, Infaq, and Shadaqah (ZIS) funds is a vital function of mosques in improving community welfare and strengthening socio-religious roles. This study aims to analyze the management of ZIS funds at Masjid Bakti, Palembang, based on planning, organizing, actuating, and controlling (POAC), and to formulate optimization strategies to enhance effectiveness, transparency, and accountability. This research employed a qualitative descriptive case study approach. Data were collected through observation, interviews, and documentation. Informants included the Chairman, Secretary, and Treasurer of Masjid Bakti. Data analysis followed Miles, Huberman, and Saldana’s model. The results indicate that ZIS fund management at Masjid Bakti has been running quite effectively, as shown by clear task division, active fund collection and distribution, and regular financial recording. However, management is not yet optimal due to weaknesses in written planning, administrative documentation, and transparency in public financial reporting. Recommended optimization strategies include developing work programs and Standard Operating Procedures (SOP), strengthening digital-based recording and reporting systems, and improving systematic supervision. These strategies are expected to make ZIS management at Masjid Bakti more effective, transparent, accountable, and sustainable.